Implementation of Legal Aid for the Poor as a Form of Practicing Pancasila Values - Choerul Amin (The Indonesian Journal of International Clinical Legal Education, 2021)
Provision of Legal Aid is one of the ways the state can achieve access to law and justice for poor people in accordance with what has been mandated by the constitution. The principle of equality before the law in the Criminal Procedure Code (KUHAP) and Article 27 paragraph (1) of the 1945 Constitution tries to be realized by the state with this legal assistance so that the poor will experience justice in law enforcement in Indonesia. Justice is the right of all Indonesian people. Justice can be obtained by all people, this is contained in the Pancasila Values ​​especially in the 5th (five) precepts which read "Social Justice for All of Indonesia". For the poor who experience legal problems in the form of injustice, they can request legal assistance from legal aid institutions that are regulated in legislation. The purpose of providing legal aid is to guarantee and fulfill the right for Legal Aid Recipients to gain access to justice, to realize the constitutional rights of all citizens in accordance with the principle of equality in law, to ensure the certainty that the implementation of Legal Aid is carried out equally across the territory of the Republic of Indonesia, and to create an effective, efficient and accountable court. The community's right to get free legal assistance (pro-bono) is regulated in Law No. 16 of 2011 concerning Legal Aid. This law regulates the communities receiving legal assistance, grants, and funding as well as legal aid mechanisms.